Effect of gastric acid‐reducing agents on the pharmacokinetics and efficacy of lemborexant. Issue 6 (2nd November 2020) - Landry, Ishani; Aluri, Jagadeesh; Hall, Nancy; Kumar, Dinesh; Dayal, Satish; Moline, Margaret; Reyderman, Larisa
Abstract: Lemborexant is a dual orexin receptor antagonist approved for treating insomnia. As the solubility of lemborexant is pH‐sensitive, the impact of the gastric acid‐reducing agent (ARA), famotidine, on lemborexant pharmacokinetics was evaluated in a Phase 1 study. Additionally, post hoc analysis of data from Phase 3 studies examined the potential effect of concomitant ARAs on patient‐reported/subjective sleep onset latency (sSOL) in subjects with insomnia. Coadministration of lemborexant 10 mg with famotidine decreased the maximum observed concentration by 27% and delayed time of maximum observed concentration by 0.5 hours. Famotidine did not affect overall lemborexant exposure based on comparison of area under the concentration curves. Concomitant ARA use in the Phase 3 studies did not impact the effect of lemborexant on sSOL; the change from baseline during the last 7 nights of 1 month of treatment with lemborexant 10 mg was −17.1 minutes with vs −17.9 minutes without ARAs. Collectively, these results indicate that lemborexant can be coadministered with ARAs. Abstract : Lemborexant is a dual orexin receptor antagonist approved for treating insomnia and being investigated as a treatment for irregular sleep‐wake rhythm disorder. The results described in this manuscript indicate that lemborexant can be coadministered with gastric acid–reducing agents (H2 antagonists/proton pump inhibitors/antacids) without dose adjustment.